Mediation in Inheritance Disputes - Kaminskienė, Natalija; Paplauskaitė, Viktorija (Magyar Rendészet, 2014)
The current opinion is that mediation is particularly suitable in the field of family disputes. Inheritance disputes are both emotionally and financially sensitive family law matters with high emotional conflict escalation level equivalent to divorce disputes. Some authors suggest that legal disputes should be described as particular disagreement in opinions, in which the claim of one party related to a legal right or a legal fact is being rejected by the other party of the dispute. The common feature of succession disputes is that these conflicts arise and are dealt with within a family circle. The concept of an extended family includes divorced people, their new and pre-existing families, registered and non-registered partnerships, children born in marriages as well as born in unregistered partnerships. Mediation is quicker than court proceedings, it is easier to appoint and hold meetings, and decisions are made faster. It is worth to emphasize that even if a peaceful agreement is not achieved, mediation can have a tremendous positive effect and benefit for both parties by opening the eyes of both the lawyer and the client to understand the core reasons of the dispute.